PELATIHAN MIRROR NEURON SYSTEM SAMA DENGAN PELATIHAN CONSTRAINT INDUCED MOVEMENT THERAPY DALAM MENINGKATKAN KEMAMPUAN FUNGSIONAL ANGGOTA GERAK ATAS PASIEN STROKE - Abdul chalik meidian; Dewa Putu Sutjana; M. Irfan (Sport and Fitness Journal, 2014)
Stroke is an interruption of blood vasculature system in the brain that causes suddenly neurological dysfunction, resulted in clinically brain tissue damage in a relatively long time period, decreased physical mobility and functional ability impaired of upper limb. The purpose of this study is to know an increasing in upper limb functional ability among stroke patients after mirror neuron system exercise and constraint induced movement therapy exercise and to know the comparison of both exercise. This study uses an experimental research with pre-test and post-test control group design. Number of samples of the first group is 13 patients given mirror neuron system exercise for 30-60 minutes , while the second group 13 patients were given constraint induced movement therapy exercise for 30-60 minutes. The research was conducted in 2 month period time. Each patient is taught a variety of upper limb functional ability in accordance with the operational concept guidance and patients were asked to repeat the exercise independently at home as directed. Measuring test of upper limb functional ability is using the wolf motor function test instruments. The result is an increase the upper limb functional ability of 21.7% in the mirror neuron system exercise group and proved a significant difference (p<0.05) and an increase in the upper limb functional ability of 17.1% in the constraint induced movement therapy exercise group and proved a significant difference (p<0.05) while the difference of increasing of upper limb functional ability of the two groups showed no significant difference (p>0,05). It was concluded that the mirror neuron system exercise is similar with constraint induced movement therapy exercise in increasing the upper limb functional ability among stroke patients.